Gas production from unsealed hydrate-bearing sediments after reservoir reformation in a large-scale simulator. (15th January 2022) - Sun, Yi-Fei; Cao, Bo-Jian; Zhong, Jin-Rong; Kan, Jing-Yu; Li, Rui; Niu, Jing-Shuo; Chen, Hong-Nan; Chen, Guang-Jin; Wu, Guo-Zhong; Sun, Chang-Yu; Chen, Dao-Yi
Highlights: The effect of reservoir reformation on hydrate exploitation was studied in a large-scale simulator. Gas-water ratio increased by 3–5 times through reservoir reformation. An ultra-high CO2 storage ratio of 79.5% was achieved. The hydrates spatiotemporal evolution process during depressurization was demonstrated. Abstract: Nowadays, the combination of natural gas hydrates exploitation and CO2 storage is considered of excellent application. In this work, we explored reservoir reformation technology to enhance gas recovery from the unsealed water-saturated hydrate-bearing deposits in a large-scale tridimensional simulator. Firstly, recurrent CO2 injection into the overburden was to gradually form CO2 hydrate and reduce its permeability. Then traditional depressurization operations were conducted to compare the influences of overburden thickness and additional reservoir reformation on the evolution of pressure distribution and the gas/water production. The results showed that reservoir reformation could effectively improve the mining efficiency, reaching ∼2–4 times of gas production and ∼3–5 times of gas–water ratio compared with the direct depressurization. After a long-term reformation, CH4 recovery ratio was increased from 24.5% to 84.9%. Additionally, we further demonstrated the complete spatiotemporal evolution mechanism of the initial CH4 hydrate and artificial overlying CO2 hydrate during depressurization. A large amount of CO2 was ultimately stored in the depleted reservoir in the form of CO2 hydrate and the CO2 storage ratio was up to 79.5%. Therefore, this reservoir reformation approach is greatly promising for high-efficient and safe exploitation of marine hydrate and CO2 storage.